Intellectual capital management paradigm for Malaysian SMEs in Kuching, Sarawak - Muhammad Khalique, Muhd Sadique; Abu Hassan, Md. Isa; Jamal Abdul Nassir, Shaari (2013)
Previous studies rarely examined the role of intellectual capital in SMEs in Malaysia. In addition, most studies neglect the SMEs operating in Kuching, Sarawak. The main crux of this paper is to explore the role of intellectual capital management as an integral element of electronics organizations in Kuching, Sarawak, Malaysia. Intellectual capital management plays a critical role for the development and sustainable of small and medium enterprises. In the beginning of the twenty first century, intellectual capital management attained significant attention from academicians, researchers and practitioners. Therefore, it is indispensible to examine the role of intellectual capital in SMEs.